A combination of nanodiamond and boron nitride for the preparation of polyvinyl alcohol composite film with high thermal conductivity. (7th October 2020) - Zhao, Kechen; Liu, Gang; Cao, Wenxin; Su, Zhenhua; Zhao, Jiwen; Han, Jiecai; Dai, Bing; Cao, Kangli; Zhu, Jiaqi
Abstract: With the advent of the 5G era, the efficient and large-scale preparation of high thermal conductivity materials is viewed as a challenge in the heat conduction and dissipation of electronic components. In this work, poly (diallyl dimethyl ammonium chloride) (PDDA) was used to combine nanodiamond (ND) particles with boron nitride nanosheets (BNNS) by electrostatic interactions. The filler and polyvinyl alcohol (PVA) were mixed to prepare a large-area, flexible, insulating, and high thermal conductivity composite film by the doctor blade method. Considering the high cost of ND, when keeping the filler content at 30 wt%, the introduction of few ND on BNNS (ND/BNNS, 3/100, w/w) enhanced the in-plane thermal conductivity of the composite film from 11.29 to 15.49 W/m·K (pure PVA film~0.22 W/m·K). Given these advantages, this composite film shows promising applications in next-generation portable and flexible electronic devices. Graphical abstract: Image 1 Highlights: Exfoliation and surface modification of h-BN. Combination of BNNS and ND through electrostatic force. BNNS and ND were combined to enhance the thermal properties of polyvinyl alcohol composite film.